2015
DOI: 10.1038/srep09632
|View full text |Cite
|
Sign up to set email alerts
|

Polymer immobilized Cu(I) formation and azide-alkyne cycloaddition: A one potreaction

Abstract: During the polymerization of aniline using copper sulphate, act as an oxidizing agent, the in-situ synthesized Cu(I) ion catalyzed the cyclo-addition between azides and alkynes. This work represents the merging of two steps, synthesis of the catalyst and application of the catalyst, in a one pot reaction. The elimination of the separate catalyst synthesis step is economic in terms of cost and time. As aniline was used as one of the reactant components so there is no requirement to use additional base for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
0
31
3
Order By: Relevance
“…In the spectrum (b), a characteristic peak at 1027 cm −1 represents the vibration of ‐C‐O‐C‐ in MPEG‐doped Cu (I)‐polyaniline. The detailed characterization of the Cu (I)‐polyaniline system is available elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spectrum (b), a characteristic peak at 1027 cm −1 represents the vibration of ‐C‐O‐C‐ in MPEG‐doped Cu (I)‐polyaniline. The detailed characterization of the Cu (I)‐polyaniline system is available elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…In association with our ongoing research on the development of efficient catalysts for the azide‐alkyne cycloaddition reaction, we have found the crucial role of light energy on the yield of the reaction . Due to the light excitation, the conduction band electron of the Cu (I) sulfide quantum dot acts as a scavenger of the terminal proton of the alkyne in the presence of organic azide with the formation of 1,4‐disubstituted 1,2,3‐triazoles, where the Cu (I) species of Cu 2 S acts as a catalyst for the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Little activation has also been observed when the reaction was performed under dark conditions in the absence of base molecule, which is due to the presence of amine group in the g CN structure, as confirmed by infrared spectroscopy analysis (electronic supplementary material, figure S1 b ), that can scavenge the proton from the alkyne molecule for the copper–acetylidine complex formation. In our previous study, we showed that amine group from aniline is also responsible for the deprotonation mechanism for the azide–alkyne cycloaddition reaction [33]. To confirm the above observation, we have selected titanium dioxide based system, a photoactive material [40], loaded with 5 wt% copper (Cu-TiO 2 ) and used it for the title reaction under similar conditions to the Cu- g CN system.…”
Section: Discussionmentioning
confidence: 96%
“…The 1 H NMR spectrum of compound (6) showed a multiplet at δ5.38 for the six Olefinic protons (-CH=CH-), a multiplet at δ2.09 for the 12 protons (-CH 2 -C=), a multiplet at δ1.34 for the other eight protons of methylene groups and at δ0.9 for the two terminal methyl groups [16]. The 13 C NMR spectrum had confirmed the result because the carbon of the acetyl group was disappeared.…”
Section: 3mentioning
confidence: 99%